Review Article: Beowulf: A new translation. By Maria Dahvana Headley. FSG Originals, 2020. Pp. 176. - Olesiejko, Jacek (Studia Anglica Posnaniensia, 2021)
Review Article: Beowulf: A new translation. By Maria Dahvana Headley. FSG Originals, 2020. Pp. 176.